From Blood Sugar To Brain Health: Understanding Type 3 Diabetes and Alzheimer’s - Moitra, Ritam; Srinivas Nayak, Sp; Lokhandwala, Zainab; Desai, Vishwa; P Patel, Harsh; Patel, Nivedita; Vansh Sanjaykumar, Dave; Jigneshbhai Patel, Keya (Journal of Neonatal Surgery, 2025)
Alzheimer’s Disease (AD), a progressive neurodegenerative disorder, has prominently been recognized as a metabolic disorder with striking similarities to Type 2 Diabetes Mellitus (T2DM), giving rise to the term “Type 3 Diabetes Mellitus” (T3DM). This designation stems from an ever-escalating repository of evidence concerning insulin resistance, impaired glucose metabolism, and mitochondrial dysfunction of the brain cells to the pathogenesis of AD. Insulin mediates a crucial role in synaptic plasticity, memory formation, alongside thrival of neurones. In both AD and T2DM, insulin signalling is disrupted, leading to neuroinflammation, oxidative stress, and accumulation of β-amyloid and hyperphosphorylated tau—core pathological hallmarks of AD. Studies have also shown that peripheral insulin resistance may exacerbate central insulin dysfunction, further implicating metabolic dysfunction in AD progression. The detection of advanced glycation end products (AGEs) and islet amyloid polypeptide (IAPP) in the AD brain, typically seen in diabetic patients, reinforces this association. Moreover, antidiabetic medications such as metformin, GLP-1 receptor agonists, and intranasal insulin have demonstrated potential in improving cognitive outcomes, indicating a therapeutic overlap. Recognizing AD as T3DM provides a novel perspective that bridges endocrinology and neurology, potentially improving diagnostic approaches and enabling more targeted treatment strategies.